Chapter 8 Brecht as a Model for Cultural Development East German ITI Events for Theatre Artists from the "Third World" - Sturm, Rebecca (Taylor & Francis, 2024)
Despite the non-governmental status of the UNESCO-affiliated International Theatre Institute (ITI), its organisational structures enabled its member states to use it as an instrument of cultural representation for national and Cold War purposes. In the late 1970s and early 1980s, the East German national centre of the ITI hosted several seminars and colloquia for theatre artists from the Global South. These events focussed heavily on playwright Bertolt Brecht as a figurehead of East German theatre since his plays and theories were of great interest to the international theatre community. This chapter examines how the GDR centre used the international community of the ITI to find and contact artistically and politically suitable participants from emerging countries and how they conceptualized and adjusted their presentation of Brecht's work and methods not only according to their participants' needs, but also to build a specific national brand of soft power designed to appeal to artists and cultural policy makers in the non-aligned countries: the GDR and the East German artists as partners and supporters of nation building.